Tribal culture, Traditional Knowledge and Forest Management in India: An Environmental Justice Perspective on Forest Rights Act - Kumar, Kamal (Indian Forester, 2022)
This paper seeks to examine the “Scheduled Tribes and Other Traditional Forest Dwellers (Recognition of Forest Rights) Act, 2006”-popularly known as 'Forest Rights Act'-and its subsequent amendment brought in 2012, from the environmental justice perspective. The main purpose of this study is to analyse its environmental justice content with special reference to the state's approach towards tribals' local cultural practices and traditional knowledge possessed by the forest communities especially tribals-in the forest management. The study adopts the social environmental justice perspective as its analytical framework to explore to what extent the customary and cultural practices as well as the values and beliefs systems based traditional knowledge of tribal communities living in India find any articulation in the exiting forest legal structure.